2005
DOI: 10.1086/426027
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Effects of Consuming a Synbiotic Containing Bifidobacterium bifidum, Bifidobacterium lactis, and Oligofructose in Elderly Persons, Determined by Real-Time Polymerase Chain Reaction and Counting of Viable Bacteria

Abstract: Synbiotic consumption increased the size and diversity of protective fecal bifidobacterial populations, which are often very much reduced in older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
103
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(112 citation statements)
references
References 33 publications
7
103
0
2
Order By: Relevance
“…Since members of B. lactis were also detected during the placebo period (in 46% of Physiological effects of probiotic yoghurt A Klein et al all subjects), this taxon may represent a component of the resident microbiota in these subjects. In recent human studies, B. lactis was detected in biopsy and faecal samples (Bartosch et al, 2005;Mättö et al, 2006). The increased numbers of B. lactis after 5 weeks of probiotic consumption may be a consequence of the good adhesion properties of this probiotic bacteria that have been shown in vitro by Ouwehand et al (1999).…”
Section: Discussionmentioning
confidence: 92%
“…Since members of B. lactis were also detected during the placebo period (in 46% of Physiological effects of probiotic yoghurt A Klein et al all subjects), this taxon may represent a component of the resident microbiota in these subjects. In recent human studies, B. lactis was detected in biopsy and faecal samples (Bartosch et al, 2005;Mättö et al, 2006). The increased numbers of B. lactis after 5 weeks of probiotic consumption may be a consequence of the good adhesion properties of this probiotic bacteria that have been shown in vitro by Ouwehand et al (1999).…”
Section: Discussionmentioning
confidence: 92%
“…was found to increase the total number of bifidobacteria in faecal samples (Bartosch et al, 2005). In another study, it was shown that 8 g/day of short-chain FOS from sucrose also caused an increase in Bifidobacterium spp.…”
Section: Elderly Peoplementioning
confidence: 90%
“…To establish that a probiotic has an effect on intestinal health, isolation of the probiotic from the stool is considered an important trait. Several studies document the ability of BB-12 ability to survive intestinal transit, which was considered an important criterion for use (Fukushima et al, 1997;Malinen et al, 2002;Ouwehand et al, 2004;Bartosch et al, 2005). Furthermore, BB-12 has been shown to impact immune function as well as impact absences from daycare for infants (Fukushima et al, 1998;Weizman et al, 2005;Kekkonen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%